Using Cartesian genetic programming to design wire antenna. (4th June 2012) - Yu, Zhangyi; Zeng, Sanyou
This paper presents a new method which uses Cartesian genetic programming (CGP) in order to design wire antenna. Since Julian F. Miller proposed the method of CGP, the research and development of CGP mainly trends in the design of the circuit application in recent years; very few scholars have the related research of wire antenna design in this field. Therefore, the most important feature in this paper is that this is the first time to apply CGP which is originally used for circuit design to make wire antenna design. By numerical test experiments and comparison, we find that this method of wire antenna design is novel and the designed wire antenna also can meet the requirements. This method has the comparative advantages and it is intelligent (self–adaptive, self–organising, self–learning, self–healing, etc.) while it can greatly increase the system speed.